2018
DOI: 10.1111/liv.13963
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic autoimmune diseases in patients with autoimmune hepatitis and their relatives: A Danish nationwide cohort study

Abstract: Danish patients with autoimmune hepatitis were highly prone to extrahepatic autoimmune diseases, but their relatives were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The question of associated diseases is also of scientific interest: The degree of disease association may point towards common risk factors, both genetic and environmental, as family members share more than their genes, often having spent many years in the same household, eating similar food, being exposed to the same infections, the same environmental toxins and often similar health behaviour. In this issue, Grønbæk et al analyse autoimmune diseases associated with autoimmune hepatitis (AIH) in patients with AIH and their first‐ and second‐degree relatives.…”
supporting
confidence: 76%
“…The question of associated diseases is also of scientific interest: The degree of disease association may point towards common risk factors, both genetic and environmental, as family members share more than their genes, often having spent many years in the same household, eating similar food, being exposed to the same infections, the same environmental toxins and often similar health behaviour. In this issue, Grønbæk et al analyse autoimmune diseases associated with autoimmune hepatitis (AIH) in patients with AIH and their first‐ and second‐degree relatives.…”
supporting
confidence: 76%
“…A concordance of AIH in twins and AIH family accumulation were evident in a recent epidemiological study, and extrahepatic autoimmune diseases have been frequently observed in AIH patients [31][32][33], suggesting common genetic risk factors for AIH and other autoimmune diseases. Although HLA is the strongest genetic risk factor for AIH, other genetic factors associated with non-HLA genes have also been reported (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary IgAN associated with autoimmune disorders, including Sjogren’s disease, ankylosing spondylitis and coeliac disease, has been reported in the literature[ 2 , 12 , 13 ]. However, IgAN with AIH has been reported in only a limited number of patients, and most of them had other autoimmune diseases such as Sjogren’s disease which is often reported to be associated with IgAN[ 14 , 15 ]. In our case, two different diseases that do not share a common pathogenesis were diagnosed sequentially.…”
Section: Discussionmentioning
confidence: 99%